Rituximab for Children With Difficult-to-Treat Nephrotic Syndrome: Its Effects on Disease Progression and Growth - Topaloğlu, Rezan; Gülhan, Bora; Çelegen, Kübra; İnözü, Mihriban; Hayran, Mutlu; Düzova, Ali; Ozaltin, Fatih (Frontiers in Pediatrics, 2019)
Background: Since the early 2000s rituximab (RTX) has been thought of as an alternative treatment for steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS). Objective: This study aimed to determine the effects of RTX treatment on disease outcome and growth in pediatric SSNS and SRNS patients. Materials and Methods: The medical records of pediatric SSNS and SRNS patients that began RTX treatment at the mean age of 10.8 ± 5.1 years between 2009 and 2017 were retrospectively reviewed. Additionally, the effect of RTX on growth was evaluated based on patient height, weight, and BMI z scores. Results: The study included 41 children, of which 21 had SSNS and 20 had SRNS. Mean age at diagnosis of NS was 5.8 ± 4.7 years. Mean duration of post-RTX treatment follow-up was 2.3 ± 1.6 years. Among the SSNS patients, 6 and 11 patients were steroid free and calcineurin inhibitor free at the last follow-up visit, respectively. The 1-year cumulative steroid and calcineurin inhibitor doses both decreased after RTX treatment, as compared to before RTX (P = 0.001 and P= 0.015, respectively). The median height z score at the time of RTX initiation was –1.2 and the median height z score at the last follow-up visit was –0.6 (P = 0.044). The median BMI z score decreased from 1.6 (IQR; 0.9-3.0) at the time RTX was initiated to 1.1 (IQR; ((-0.7)-2.5) at the last follow-up visit (P = 0.007). At the last follow-up visit 4 SRNS patients had complete remission and 4 had partial remission. The 1-year cumulative steroid dosage in the SRNS patients decreased significantly after RTX, as compared to before RTX (P = 0.001). The median height z score at the time of RTX initiation was –0.8 and the median height z score at the last follow-up visit was –0.7 (P = 0.81). The median BMI z score decreased from 0.3 at the time RTX was initiated to –0.1 at the last follow-up visit (P = 0.11). Conclusion: RTX has a more positive effect on disease outcome and growth in SSNS patients than in those with SRNS.